Detecção precoce de atraso neuromotor e déficits neurológicos em lactentes de risco biológico nos primeiros quatro meses de vida: estudo longitudinal - Paz, Monique Maria Silva da (2024)
Typical motor development can be negatively influenced by biological risk factors. Monitoring the neuromotor development of these infants is essential to perform early detection of neuromotor delays and/or deficits in a qualitative and quantitative manner to predict future neuromotor outcomes. To our knowledge, this is the first study to simultaneously use the GMA, MOS-R, HINE, and IMP to understand neuromotor development. Thus, the objective of this study was to detect neuromotor delays or deficits early in the first four months of life in infants at biological risk. To this end, a cohort study was carried out, in which 30 infants were included in the risk group and 30 healthy full-term infants were included in the control group. The infants were assessed at two, three and four months and reassessed at six months of age. In addition to the Identification Form and the Affordances in the Home Environment for Motor Development – Infant Scale questionnaire, four other assessment instruments were used: the General Movements Assessment, The Motor Optimaly Score – Revised, Hammersmith Infant Neurological Examination and Infant Motor Profile. Statistical analysis was performed using the Statistical Package for the Social Sciences and R Studio, with a significance level of 5%. It was possible to clearly demonstrate the effectiveness of early detection of neuromotor delays and/or deficits in the first four months of life in infants at biological risk to predict neuromotor outcome at six months. Signs of neuromotor alterations were observed in the first months, allowing us to infer which deficits in neuromotor performance are present in the biological risk groups and in full-term infants during the sixth month. In addition to the total scores of the instruments used at two, three, and four months of age, their subscores/domains were able to predict the risk of developmental delay. Among the four instruments, the HINE presented the best predictive capacity, being included as a predictor variable in all six regression models conducted in this study. Furthermore, the correlations between the environmental factors assessed by AHEMD-IS and the neuromotor results highlighted the importance of environmental enrichment for neuromotor development in the first six months of life. Given this, the need for early detection of neuromotor delays or deficits in infants at biological risk before four months of age is undeniable, enabling the implementation of early intervention programs during periods of greatest neuroplasticity.